A Revised Mental Energy Hypothesis of the g Factor in Light of Recent Neuroscience - Debatin, Tobias (Review of General Psychology, 2019)
The article proposes a revised mental energy hypothesis for the emergence of the g factor. Charles E. Spearman interpreted the g factor as a kind of domain-general mental energy. Nowadays, it is known that the energy currency of organisms is the chemical energy transporter adenosine triphosphate (ATP). ATP is produced by complex metabolic processes (mainly by glucose oxidation), and most of it in the human brain is used for neural signaling. There are substantial individual differences in the metabolic properties of the brain, which lead to different levels of energy production. It is thereby proposed to place more emphasis on individual differences of metabolic functions in intelligence research. Neuroscientific findings suggest that increased brain metabolism and, therefore, higher energy-production levels facilitate better performance on different cognitive tasks. These findings are not in conflict with the refined neural efficiency hypothesis. In addition, building on Dennis Garlick’s proposal that neural plasticity is the core process underlying the development of the g factor, it is illustrated why ATP is crucial for neural plasticity. Taken together, the direct effects of level of energy production on cognitive performance and the relations with neural plasticity suggest an important role in the emergence of the g factor.
CRIS-Team Scopus Importer:2019-05-02
Keywords: energy metabolism; g factor; intelligence; neuroimaging

Does fluid intelligence facilitate the learning of English as a foreign language?-A longitudinal latent growth curve analysis - Debatin, Tobias; Harder, Bettina; Ziegler, Albert (Learning and individual differences, 2019)
The relationship between intelligence and learning is still a controversial topic. The study at hand examined, via growth curve analysis, if fluid intelligence predicts long-term learning rates of foreign language acquisition in English. From the beginning of grade 5 to the middle of grade 7, N = 521 students were tested four times with Rasch-scaled English achievement tests. Intrinsic motivation was measured as a control variable. Fluid intelligence and intrinsic motivation were found to be related to the initial level of English achievement. However, neither fluid intelligence nor intrinsic motivation predicted the rate of change concerning the English scores. These findings extend the growing body of evidence that the relation between intelligence and rate of academic long-term learning may not be as strong as traditionally expected.
CRIS-Team WoS Importer:2019-04-16

Erste Schritte zu einer systemischen Begabungsdiagnostik: Ein Paradigmenwechsel von der Potenzialfeststellung zur Exzellenzvorhersage - Stöger, Heidrun; Debatin, Tobias; Ziegler, Albert (Begabungen und Talente (Tests und Trends - Jahrbuch der pädagogisch-psychologischen Diagnostik, 2017)

Intelligence, Educational and Learning Capital, and Domain Impact Level of Activities as Predictors of School Achievement - Harder, Bettina; O'Reilly, Colm; Debatin, Tobias (Journal for the education of the gifted, 2018)
Intelligence is a well-supported predictor of school achievement, however, it refers only to the cognitive facet of learning determinants. The aim of this article is to contrast the predictive properties of two comprehensive concepts developed within the actiotope model of giftedness (AMG) with that of intelligence. These concepts are educational and learning capital (ELC) and the domain impact level of activities (DILA), which were contrasted with a nonverbal intelligence measure (Raven’s standard progressive matrices). We investigated N = 90 fourth graders from regular classes in a German urban area. Results showed that achievement in German language was better predicted by ELC and DILA than by intelligence, whereas mathematical achievement was predicted by intelligence and educational and learning capital to similar degrees. The AMG concepts also showed incremental predictive power over intelligence. These findings suggest that ELC and, with some limitation, DILA (a) are well suited for predictions of school achievement and (b) capture valuable different aspects of the learning system than intelligence measures. Implications for education and research are discussed.
Created from Fastlane, Scopus look-up
Keywords: domain impact level of activities; educational and learning capital; intelligence; performance prediction; school achievement

Learning resources and talent development from a systemic point of view - Ziegler, Albert; Debatin, Tobias; Stoeger, Heidrun (Annals of the New York Academy of Sciences, 2019)
System theories postulate that a system needs resources in order to evolve and function as an entirety. According to the actiotope model of giftedness, exogenous and endogenous resources needed to develop excellence include five forms of educational capital (economic, cultural, social, infrastructural, and didactic) and five forms of learning capital (organismic, telic, actional, episodic, and attentional), independent of domain and level of talent development. In three studies, we addressed several blind spots in the empirical basis of the educational and learning capital (ELC) approach. The studies were conducted in different domains, with different samples, and on various levels of talent development, as well as with regard to different functions for which resources can be used. Study 1, comprising 365 sixth graders, showed that ELC have an incremental validity beyond IQ for predicting scholastic achievement. In study 2 with 90 women holding a university degree in science, technology, engineering, and mathematics (STEM), we provide evidence that in the collegiate actiotopes of women who were later successful in STEM, more ELC had been available and was used to serve different functions than in the actiotopes of less successful women in STEM. In study 3 with 74 long-distance runners, we found a similar pattern of results for different achievement levels in an athletics domain.
CRIS-Team Scopus Importer:2019-06-18
Keywords: actiotope; educational capital; learning capital; learning resources; talent development

Why Experts Can Do What They Do: The Effects of Exogenous Resources on the Domain Impact Level of Activities (DILA). - Debatin, Tobias; Hopp, Manuel; Vialle, Wilma; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)
In many domains, it is estimated that approximately 10,000 hours of planned learning activities are required to reach an expert level of performance. However, this poses a challenge for learners to balance such extensive learning times with the demands of everyday life. In our study we focused on activities in the domain of chess. We hypothesized that chess-related activities could be better integrated in an individual’s life if exogenous resources – specified in the educational capital approach (Ziegler & Baker, 2013) – are sufficiently available. In order to test this hypothesis we introduced the concept of the Domain Impact Level of Activities (DILA), that is, the degree to which a learner's activities are influenced by a certain domain. As expected, we found that the more exogenous resources (educational capital) chess players had at their disposal, the higher was their DILA in regard to social and everyday activities. Concerning social activities, we also found a direct effect of playing time hours and a small indirect effect of educational capital on the DILA via playing time hours. In the model predicting the DILA of everyday activities, these effects were not found. It was concluded that the availability of educational capital facilitates the integration of domain-related activities in a learner’s life.
Keywords: Educational capital; actiotope; chess; expertise